Management of Non-Radiographic Axial Spondyloarthritis Cases with IL-17A Inhibitors - I Putu Yogi Sastrawan; Dewa Ayu Kartika Tejawati; Pande Ketut Kurniari (Indonesian Rheumatology Associantion, 2026)
A B S T R A C T Background: Non-radiographic axial spondyloarthritis (nr-axSpA) is a key subgroup within the spondyloarthritis (SpA) spectrum, recognized via the ASAS classification criteria. Treatment options for nr-axSpA are similar to AS and include nonsteroidal anti-inflammatory drugs, tumor necrosis factor-alpha inhibitors, and IL-17A inhibitors. Secukinumab, a fully human monoclonal antibody, targets and neutralizes IL-17A, and is the first IL-17A inhibitor approved for AS treatment. Case Presentation: This case involves a 34-year-old male with non-radiographic axial spondyloarthritis. The patient presented with chronic back pain and stiffness, mainly in the sacroiliac joints. Initial treatments were inadequate, leading to the administration of secukinumab. The patient showed significant clinical improvement following secukinumab treatment, indicating its efficacy in managing nr-axSpA. Conclusion: This case demonstrates the potential benefits of secukinumab in treating non-radiographic axial spondyloarthritis. As the first IL-17A inhibitor approved for AS, secukinumab offers a promising therapeutic option for nr-axSpA patients, providing substantial symptom relief and enhancing quality of life. Further research is needed to assess the long-term efficacy and safety of secukinumab in this patient population.